Customer Engagement as the Key to Customer Loyalty in Saung Apung Harvest City Restaurant - Nuriyati Samatan; Mulharnetti Syas; Robingah; Jun Firmansyah; A. Saifulloh (Greenation Research & Yayasan Global Resarch National, 2025)
This study aims to determine customer engagement as the key to customer loyalty at Saung Apung Harvest City Restaurant. This study used the Two-Way Symmetrical Model, which emphasizes mutual understanding between organizations and their publics. The research is qualitative, using the Constructivism paradigm, with field data collection conducted through observation, interviews, and documentation. The results of the study found that two-way communication between management and customers builds customer engagement in providing information, comments, and suggestions to management for the improvement and enhancement of the restaurant's performance, ambience, and the taste of the food and beverages served. Saung Apung Restaurant is also unique in that it is located quite far from the center of town, with no physical signs indicating its presence, yet customers still choose to visit and enjoy the dishes served at Saung Apung Restaurant. Management also strives to build good relationships with customers to increase loyalty and ensure the growth and sustainability of the restaurant in a highly competitive market.